Capture and Accumulation of Perchlorate in Lettuce. Effect of Genotype, Temperature, Perchlorate Concentration, and Competition with Anions - Escudey-Castro, A; Escudey-Castro, A (Elsevier Ltd, 2014)
Various studies have evaluated the accumulation of ClO4 - in lettuce (Lactuca sativa), but very few have dealt with the variables that can interfere with its capture. The present study evaluates the transfer of ClO4 - in two L. sativa varieties: butter head (L. sativa var. capitata) and cos lettuce (L. sativa var. crispa) under hydroponic conditions. The ClO4 - concentrations used correspond to levels (1 and 2mgL-1), measured in irrigation water in the Iquique region in the north of Chile. Results indicate that the capture of ClO4 - is dependent on its concentration, lettuce genotype, and temperature. The butter head variety accumulates the highest perchlorate concentrations. Anion competition involving NO3 - (16 and 48mM), Cl- (23 and 56mM), and SO4 2- (10 and 20mM) was evaluated, being NO3 - (48mM), the most significant competition reducing the concentration of ClO4 - in tissues of L. sativa varieties. © 2014 Elsevier Ltd.